Natal - palco de tensões, bastidores de conflitos: uma sociologia política do Plano Diretor de Natal/RN - Maria, Anne Caroline Araújo de (2022)
As well as in other Brazilian cities, Natal in Rio Grande do Norte underwent a review of its Municipal Master Plan, which involves controversies in the local public sphere. Once the Master Plan is an instrument for planning and ordering the urban territory, assisting in the formulation of public policies, the document in Natal was at the height of its revision, when different actors articulated themselves on various stages and backstage, giving voice to what they think it is “good” and “fair” for the city. In this collective struggle that involves issues of economic and social justice, under the prism of divergent ideologies and interests, State and society relate and also tension, taking the problem to the field of political sociology, more precisely to the agenda of the sociology of problems. From the mobilization of groups that seek to give voice to their concerns, the situation changes in a political process, which is not restricted to public discussion, but goes beyond an institutional, legal and political ecology to be considered a public arena. Therefore, this research sought to develop an investigation of the ways in which the actors involved in the public controversy surrounding the Natal Master Plan were mobilized. For this, an investigation of a qualitative nature was carried out, using documental research, direct and participant observation, as well as observations of interaction in social networks. The theoretical principles were built from a dialogue between the research agenda of the Sociology of Public Problems (Daniel Cefaï), Sociology of Criticism (Luc Boltanski and Laurent Thévenot) and Critical Theory (Jürgen Habermas and Nancy Fraser). Through the analyzed scenes, it was possible to investigate the tensions and build an argumentative repertoire of some of the actors, who were categorized among state, market and civil society actors, and also to perceive which forces stand out in this ecology of public experience.